DNA metabarcoding unveils the effects of habitat fragmentation on pollinator diversity, plant‐pollinator interactions, and pollination efficiency in Maldive islands - Nicola Tommasi; Paolo Biella; Davide Maggioni; Luca Fallati; Giulia Agostinetto; Massimo Labra; Paolo Galli; Andrea Galimberti (Molecular Ecology, 2023)
Habitat fragmentation affects biodiversity, but with unclear effects on pollinators and their interactions with plants in anthropized landscapes. Islands could serve as open air laboratories, suitable to disentangle how land‐use alteration impacts pollination ecology. In Maldive islands we investigated how pollinator richness, plant‐pollinator interactions and pollination efficiency are influenced by the green area fragmentation (i.e., gardens and semi‐natural patches). Moreover, we considered the mediating role of pollinator body size and the plant trait of being invasive in shaping interactions. To do this, we surveyed pollinator insects from 11 islands representing a gradient of green area fragmentation. A DNA metabarcoding approach was adopted to identify the pollen transported by pollinators and characterize the plant‐pollinator interactions. We found that intermediate levels of green area fragmentation characterized pollinator communities and increased their species richness, while decreasing interaction network complexity. Invasive plants were more frequently found on pollinator bodies than native or exotic noninvasive ones, indicating a concerningly higher potential for pollen dispersal and reproduction of the former ones. Intriguingly, pollinator body size mediated the effect of landscape alteration on interactions, as only the largest bees expanded the foraging diet in terms of plant richness in the transported pollen at increasing fragmentation. In parallel, the pollination efficiency increased with pollinator species richness in two sentinel plants. This study shows that moderate landscape fragmentation of green areas shapes many aspects of the pollination ecosystem service, where despite interactions being less complex and mediated by pollinator body size, pollinator insect biodiversity and potential plant reproduction are supported.